Heteroatom Doping Synergistic Iron Nitride Induced Charge Redistribution of Carbon based Electrocatalyst with Boosted Oxygen Reduction Reaction. Issue 1 (21st December 2022) - Guo, Yuyu; Xu, Dianyu; Li, Shuting; Han, Jinxi; Yang, Qi; Xia, Zhengqiang; Xie, Gang; Chen, Sanping; Gao, Shengli
Abstract: Oxygen reduction reaction (ORR) is Achilles' heel of zinc‐air battery. The ideal electrocatalyst for ORR should combine both high activity and high stability. In order to achieve this goal, a new N, S co‐doped carbon coated Fe3 N nanoparticles electrocatalyst with redistributed charge was designed and synthesized. The doping of S elements destroyed the ordered structure of carbon matrix, which cooperated with Fe3 N nanoparticles to cause charge redistribution of carbon atoms. Furthermore, the carbon shell protected Fe3 N from corrosion during the electrocatalytic process. Fe3 N/NSC electrocatalyst showed excellent ORR property with E 1/2 =0.86 V, and the zinc‐air battery assembled based on it could run stably for more than 650 hours. This work provides a strategy to regulate the redistributed charge of carbon atoms to boost its electrocatalytic activity and stability together. Abstract : Carbon shelter : Fe3 N@NSC with high activity and excellent stability was synthesized by a facile process. The high activity was obtained due to the co‐doping of N and S into carbon matrix collaboratively with Fe3 N that lead to the outflow of electrons from carbon, and the exposure of more positive charges on carbon atoms. Carbon shell protected Fe3 N from corrosion during the electrocatalytic process and afforded its excellent stability. Thus, the zinc air battery (ZAB) assembled with Fe3 N@NSC as cathode showed great potential for practical applications.